Engagement with eHealth Self-Monitoring in a Primary Care-Based Weight Management Intervention - Wolin, Kathleen Y. (PLoS One, 2015)
BACKGROUND: While eHealth approaches hold promise for improving the reach and cost-effectiveness of behavior change interventions, they have been challenged by declining participant engagement over time, particularly for self-monitoring behaviors. These are significant concerns in the context of chronic disease prevention and management where durable effects are important for driving meaningful changes. PURPOSE: “Be Fit, Be Well” was an eHealth weight loss intervention that allowed participants to self-select a self-monitoring modality (web or interactive voice response (IVR)). Participants could change their modality. As such, this study provides a unique opportunity to examine the effects of intervention modality choice and changing modalities on intervention engagement and outcomes. METHODS: Intervention participants, who were recruited from community health centers, (n = 180) were expected to self-monitor health behaviors weekly over the course of the 24-month intervention. We examined trends in intervention engagement by modality (web, IVR, or changed modality) among participants in the intervention arm. RESULTS: The majority (61%) of participants chose IVR self-monitoring, while 39% chose web. 56% of those who selected web monitoring changed to IVR during the study versus no change in those who initially selected IVR. Self-monitoring declined in both modalities, but completion rates were higher in those who selected IVR. There were no associations between self-monitoring modality and weight or blood pressure outcomes. CONCLUSIONS: This is the first study to compare web and IVR self-monitoring in an eHealth intervention where participants could select and change their self-monitoring modality. IVR shows promise for achieving consistent engagement.